2013
DOI: 10.3109/1547691x.2013.816394
|View full text |Cite
|
Sign up to set email alerts
|

Oral tungstate (Na2WO4) exposure reduces adaptive immune responses in mice after challenge

Abstract: Tungstate (WO²⁻₄) has been identified as a ground water contaminant at military firing ranges and can be absorbed by ingestion. In this study, C57BL6 mice were exposed to sodium tungstate (Na2WO4·2H2O) (0, 2, 62.5, 125, and 200 mg/kg/day) in their drinking water for an initial 28-day screen and in a one-generation (one-gen) model. Twenty-four hours prior to euthanasia, mice were intraperitoneally injected with Staphylococcal enterotoxin B (SEB) (20 μg/mouse) or saline as controls. After euthanasia, splenocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…In the present study, the functional activity of T CTL cells decreased at 1000 mg STD/L when splenic T CTL lymphocytes from control and STD-treated mice were sensitized to P815 mastocytoma cells ex vivo , prior to functional assessment in the effector phase. Similarly, other studies have shown that tungstate-treated C57BL/6 mice developed significant splenomegaly when inoculated with the T-cell activating RSV (Fastje et al, 2012), and demonstrated suppression of activated T H and T CTL cells, when challenged with SEB (Osterburg et al, 2014). In the absence of RVS or SEB challenge, tungstate had no effect on spleen size or T-cell populations (Fastje et al, 2012; Osterburg et al, 2014).…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…In the present study, the functional activity of T CTL cells decreased at 1000 mg STD/L when splenic T CTL lymphocytes from control and STD-treated mice were sensitized to P815 mastocytoma cells ex vivo , prior to functional assessment in the effector phase. Similarly, other studies have shown that tungstate-treated C57BL/6 mice developed significant splenomegaly when inoculated with the T-cell activating RSV (Fastje et al, 2012), and demonstrated suppression of activated T H and T CTL cells, when challenged with SEB (Osterburg et al, 2014). In the absence of RVS or SEB challenge, tungstate had no effect on spleen size or T-cell populations (Fastje et al, 2012; Osterburg et al, 2014).…”
Section: Discussionmentioning
confidence: 74%
“…Published reports indicated that sodium tungstate may modulate hematopoiesis, immune cell populations, and immune responses in rodent models (Osterburg et al, 2010, 2014; Fastje et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations